2017
DOI: 10.1136/sextrans-2017-053232.145
|View full text |Cite
|
Sign up to set email alerts
|

P101 Cutting the time to treatment of chlamydia trachomatis (CT) and neisseria gonorrhoeae (NG) with near-patient molecular diagnostics: the utility of the cepheid genexpert system

Abstract: IntroductionThe Cepheid GeneXpert® provides near-patient molecular detection of CT/NG, with results available in 90 minutes. Previous studies have illustrated the benefits to asymptomatic individuals and their partners in reducing time to treatment.MethodsA case-control study was undertaken to investigate the impact of introducing GeneXpert to a Level 3 symptomatic service. 100 patients diagnosed with CT+/-NG before and after introduction were identified. Time from attendance to treatment was measured. Using s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Implementation of the Cepheid CT/NG GeneXpert demonstrated that faster (and appropriate) treatment was achieved in all settings. This was facilitated by reduced time to notification of results, which was a specific outcome for some studies [ 47 , 58 , 60 , 63 , 69 ] but same-day treatment was hindered by patients not waiting for test results at the point of care [ 61 , 65 ], and one study specifically reported increased patient waiting time in-clinic [ 57 ]. However, implementation of the test was broadly acceptable in all settings reporting this as an outcome [ 55 , 61 , 66 68 , 72 ].…”
Section: Resultsmentioning
confidence: 99%
“…Implementation of the Cepheid CT/NG GeneXpert demonstrated that faster (and appropriate) treatment was achieved in all settings. This was facilitated by reduced time to notification of results, which was a specific outcome for some studies [ 47 , 58 , 60 , 63 , 69 ] but same-day treatment was hindered by patients not waiting for test results at the point of care [ 61 , 65 ], and one study specifically reported increased patient waiting time in-clinic [ 57 ]. However, implementation of the test was broadly acceptable in all settings reporting this as an outcome [ 55 , 61 , 66 68 , 72 ].…”
Section: Resultsmentioning
confidence: 99%